IMPLEMENTASI PEMBELAJARAN MENDALAM BERBASIS PROYEK DALAM MENINGKATKAN LITERASI DAN NUMERASI SISWA STUDI KASUS DI SMPN 3 RANCAEKEK - Waska Warta; Ima Mulhima Prihatini; Kokom Komalasari; Yulidar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
21st-century education demands that students have strong literacy and numeracy skills as a foundation for critical thinking, problem-solving, and decision-making. However, various national and international assessment results indicate that students' literacy and numeracy skills in Indonesia are still in the low category. The purpose of this study was to obtain information and analyze project-based immersive learning in improving student literacy and numeracy at SMPN 3 Rancaekek, which focused on the planning process, implementation, evaluation, follow-up plans, obstacles and solutions encountered. This study used a qualitative approach with a case study method. The results illustrate that in the planning stage (Plan), starting with identifying initial problems, formulating learning objectives, compiling an In-Depth Learning Implementation Plan (RPPM), and determining the project theme. The implementation phase (Do) begins with the presentation of the problem and an introduction to the project, information and data collection, data analysis and development of project products, presentation of results, and student activity outcomes. The evaluation phase measures improvements in literacy and numeracy through project tests and assessments, including literacy and numeracy test results, assessment of the project process and product, and student reflection. As a follow-up plan (Act), enrichment programs, remedial classes, and teacher reflections are implemented. Challenges include limited time to complete the entire project, significant differences in student literacy and numeracy skills, limited supporting facilities, uneven collaboration, and teachers' unfamiliarity with authentic assessment and project rubrics. Solutions to address these challenges include improved time management, differentiated learning, utilizing alternative resources, strengthening collaboration, and improving teacher competency.